La protection de l’environnement : un survol du cadre législatif - Yergeau, Michel; St-Denis, Jacques (Assurances, 1988)
Our collaborators, Messrs. Yergeau and Saint-Denis, present a concise summary of federal and provincial powers with respect to environmental protection rights, the progress made with respect to the legislative corpus in this area as well as the stalemates encountered where court decisions are concerned. The authors also provide an historical look back at the events which first made the society aware of the need for environmental protection and the protests which led to environmental rights as we know them today. What is implied by the term environment, how can we damage it and how is it protected by Quebec and Canadian laws – these are the questions considered by the authors, both associated with the Montreal law firm Lavery, O'Brien.